C–H functionalization of triazolo[a]-annulated 8-azapurines. Issue 21 (25th May 2016) - Gorbunov, Evgeny B.; Rusinov, Gennady L.; Ulomsky, Evgeny N.; Rusinov, Vladimir L.; Charushin, Valery N.; Chupakhin, Oleg N.
Graphical abstract: Highlights: Palladium-free direct C–H functionalization of annulated 8-azapurines. A series of phenol ethers and thiophene was used under oxidative conditions. Single crystal X-ray data for a new derivative of 8-azapurine are reported. Abstract: Direct C–H functionalization of triazolo[ a ]-annulated 8-azapurines with phenol ethers or thiophene has been performed using the oxidative nucleophilic displacement of a hydrogen on the pyrimidine ring, proceeding through the intermediacy of the corresponding σ H -adducts.